Raising the awareness of undergraduate nurses to the psychosocial impact of living with cancer: A consumer engagement in teaching initiative - Lana Zannettino; Jan Thompson; Julie Marker; Stephanie Agius (Elsevier, 2016)
This article reflects on the development and implementation of a consumer engagement in teaching initiative by the authors. The authors highlight the challenges of engaging undergraduate nursing students on the psychosocial aspects of living with cancer and other chronic illnesses when students have very limited personal and professional experiences to draw on. The authors discuss how they have responded to these challenges by integrating the voices of consumers into their classrooms. Speakers from consumer advocacy organization, Cancer Voices SA, participated in a series of tutorials in a 1 st year topic in the Undergraduate Nursing Program at the School of Nursing and Midwifery, Flinders University. Student feedback from the implementation of the initiative indicated that students found consumers' stories and experiences of living with cancer, "moving and powerful" and that they encouraged students to question their assumptions about the psychosocial impacts of cancer on individuals and families. The importance of good communication in reducing patient distress was identified by students as an important element of consumers' experiences of the health care system as was the need for transparency and information sharing between health care providers across the health care system. For many students, consumers' stories and experiences had reinforced students' commitment to studying nursing and pursuing a career in nursing. The article concludes that involving consumers in the education of health care professionals encourages a much deeper understanding of and empathy for how patients experience disease, which is integral to the provision of patient-centered and holistic care.